Modelling of Community Recovery Level of Flood-Prone Area in Surakarta - Rita Noviani; Pipit Wijayanti; Yasin Yusup (Universitas Muhammadiyah Surakarta, 2013)
This study aimed to develop community resilience velocity model after the disaster. The study is a descriptive analysis using household survey of the flood victims. Total sample of 100 households in ten villages on the banks of the Bengawan Solo River, and is an area prone to flooding. Processing for data is using descriptive statistical analysis, correlation and regression, analysis of variance and factor analysis. There is a close relationship between the power recovered by a factor of assets, knowledge and long flood events. The two main factors affecting the dominant public resilience is a characteristic of a society of social assets, knowledge and natural assets. The second factor is the economic and financial factors, and long floods. The Resulted model level resilience from the research is Y = 0.012 X1 + 0.118 X2 + 0.394 X3 + 0.079 X4 + 0.040 X5-.002 X6. which; Y is Power Restored (speed), Ownership Financial Assets (X1), Ownership of Assets Economics (X2 ), Natural Asset Ownership (X3), Social Asset Ownership (X4), Lama flooding (days) (X5), and Knowledge (X6). Further optimization of the acceleration of flood resilience of households to do with strengthening the ownership of assets, improving the capacity of communities and reduce the threat of flooding and duration of.